Pre-focused lead titanate >25 MHz single-element transducers from hollow spheres - Meyer, Richard J.; Newnham, Robert E.; Alkoy, Sedat; Ritter, Timothy A.; Cochran, Joseph K. (My University, 2001)
Miniature lead titanate (PT) hollow spheres with diameter in the 1 to 10 mm range and wall thicknesses of 20 to 120 ?m have been fabricated. Shell sections were used as components of pre-focused transducers. Spheres are produced using a new sacrificial core technique that produces hundreds of spheres with a more uniform wall thickness than those produced by earlier methods. Shells produced from these spheres were found to have a wall thickness variation of about 10%. Despite this variation, bulk properties were estimated from capacitance and impedance data. Shells tested in this work had dielectric constants (1 kHz) near 280 with loss factor of <2% and d33 values of 68 pC/N. Thickness coupling coefficients averaged 0.51 with mechanical quality factors of <15. A transducer fabricated from these sections of spheres had a round-trip insertion loss of -20.1 dB at the center frequency of 39.8 MHz and a 6 dB bandwidth of 33%. © 2008 Elsevier B.V., All rights reserved.
Keywords: Bandwidth; Capacitance; Electric impedance; Electric losses; Permittivity; Spheres; Hollow spheres; Single-element transducers; Transducers; lead; titanium; article; biomedical engineering; echography; equipment design; human; instrumentation; scanning electron microscopy; transducer; Biomedical Engineering; Equipment Design; Humans; Lead; Microscopy, Electron, Scanning; Titanium; Ultrasonography